Consumers' motivation to purchase electric vehicles: a mixed-methods belief elicitation study using theory of planned behavior - Shun Mya Thwe; Weng Marc Lim; Kian Yeik Koay; Derek Ong (Acta Psychologica, 2025)
Transportation ranks among the top sources for global carbon dioxide (CO₂) emissions. Though electric vehicles (EVs) offer a promising solution, consumer uptake remains low. The theory of planned behavior (TPB) identifies factors that drive pro-environmental behavior, yet seldom investigates the specific beliefs that inform and shape those factors. This article addresses that oversight by identifying key beliefs and investigating their relationships within an extended TPB to explain consumers' decision to purchase EVs. Semi-structured interviews with 33 consumers elicited underlying beliefs to the point of data saturation before a survey of 472 consumers was conducted and analyzed via partial least squares structural equation modeling (PLS-SEM). Specifically, this article extends the TPB by (i) identifying the behavioral and normative beliefs shaping attitudes and subjective norms toward EV purchases, (ii) investigating perceived behavioral control (PBC) as a unidimensional variable influenced by covert and overt control beliefs toward EV purchases, (iii) integrating moral norms alongside extrinsic and intrinsic religiosity as values shaping EV purchases, and (iv) inspecting the role of generations in EVs purchases. The results reveal attitude as the most influential determinant of consumers' intention to purchase EV, followed by PBC, moral norms, and subjective norms, while generational variations showed that extrinsic and intrinsic religiosity is only significant to Gen Y, but not Gen X and Gen Z, in EV purchases. These insights contribute by revealing how beliefs, values, and generational differences shape EV adoption, with practical suggestions to promote EV purchases in order to accelerate the transition to cleaner transportation.